Impacto das alterações ambientais sobre a decomposição da serapilheira em vegetação de Cerrado - Silva, Laura Vívian Barbosa (2017)
Litter decomposition is a key process for the maintenance of soil fertility, especially in nutrient poor soils, such as the Cerrado soils. Natural factors that control the decomposition process can be affected by environmental changes. The deposition of atmospheric nitrogen, the invasion of exotic species or abrupt changes in the amount of litter, for example, can affect decomposition and consequently the cycling of nutrients. Therefore, the assessment of the consequences of these environmental changes on the functioning of tropical ecosystems is essential, especially in view of their importance as reservoirs of biodiversity. The general objective of this study was to evaluate the effects of N fertilization and of invasive exotic grasses on litter decomposition and its consequences on N dynamics in Neotropical savanna (cerrado) areas. The study was conducted in the Reserva Ecologica do Panga in Uberlândia, Brazil. Decomposition rate was determined using litter bags containing 10 g of litter. To evaluate the effect of N addition in the soil on N dynamics, litter decomposition was determined in experimental plots subjected to different levels of fertilization: high N addition (50kg N ha-1 year-2), low N addition (20kg N ha-1 year-2) and control (no addition N). Moreover, chemical parameters of soil (δ15N, δ13C, N, C, mineralization and nitrification of N) and microbial (basal respiration, carbon of microbial biomass, metabolic quotient, enzyme activity) was compared between plots with different levels of nitrogen addition. To evaluate the effects of the invasion of exotic grasses, litter decomposition and litter quality was compared between areas invaded or not by the exotic grasses Melinis minutiflora and Brachiaria decumbens. Microbial parameters were also compared between the invaded and non-invaded areas. To determine the effect of litter quantity and arthropod exclusion on decomposition, litter addition, litter removal and unmanipulated control plots were established in a dry forest (cerradão) area. Results of the fertilization experiment showed that, in general, the litter of T. leiostachya decomposed faster when litter was originated from the high N addition plots. This was probably because the N foliar concentration was higher in litter grass collected in plots of high N addition than in the grass litter collected in the other treatments. In addition, litter decomposition was faster in the plots of high N addition than in plots of low N addition and control. However, these effects were variable between the years. In the 2011, four years after the beginning of the fertilization experiment, NH4+ concentration and the microbial activity in the soil did not differ between the treatments. N addition did not increased grass cover and did not caused N transformation in the soil via mineralization and nitrification. However, there was a reduction in δ15N on grass leaves growing in plots subject to high levels of N addition. In relation to the impact of invasive grasses, results showed that N concentration was smaller in the exotic species B. decumbens than in M. minutiflora or in the native grasses. Litter decomposition was faster in areas invaded by exotic grasses than in areas not invaded. The litter produced by M minutiflora decomposed slower than litter produced by B. decumbens or native grasses, both in invaded and non-invaded plots. In plots with M. minutiflora the activity of the enzyme β-glycosidase was higher, whereas soil microbial carbon was greater in B. decumbens plots. In the experiment of litter x manipulation, results showed that liter removal had a negative impact on decomposition rates, and this was true in the two years of the study. Litter removal negatively affected decomposition rates, independently of the presence or absence of macro-arthropods. In general, the results of this study showed that environmental changes affect the main controlling factors of the litter decomposition process: microclimate, litter quality and decomposer activity.